The The Implementation of the IMPROVE Learning Model Viewed from Mathematical Disposition on Students’ Mathematical Critical Thinking Ability - Elzikra Dalillah; Arnida Sari (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2026)
This research was conducted to examine the influence of the IMPROVE learning model on students’ mathematical critical thinking skills when viewed from their mathematical disposition. An experimental approach with a 2 × 3 factorial design was applied in this study. The collected data were analyzed using the Liliefors test, F-test, and two-way ANOVA. The findings revealed that the implementation of the IMPROVE learning model significantly enhanced students’ mathematical critical thinking skills. Furthermore, mathematical disposition was found to contribute to the development of these skills. The results also indicated an interaction effect between the learning model and students’ mathematical disposition. Consequently, the IMPROVE learning model can be considered an effective approach for fostering students’ mathematical critical thinking abilities.